Enhancing Organizational Performance Through Ethical Leadership and the Implementation of GCG - Suryadi, Arief; Rahmat, Nur; Purbojati, Nurrakhman; Mais, Rimi Gusliana; Sunarsih, Uun (Santoso Academy Network, 2025)
This study aims to analyze the effect of ethical leadership and implementation of good corporate governance (GCG) on improving the performance of State-Owned Enterprises (BUMN) from a financial and non-financial perspective, with a case study at PT Adhi Karya (Persero) Tbk. This study uses primary data through questionnaires distributed to company employees, with data processing using the SPSS statistical method. The results of the study indicate that ethical leadership does not have a significant effect on BUMN performance, while GCG implementation has a positive and significant effect on that performance. These findings highlight that the application of the principles of transparency, accountability, and sustainability in corporate governance plays a key role in improving operational efficiency and achieving the company's strategic goals. The managerial implications of this study include the need to strengthen GCG implementation at all levels of the organization to improve company performance. Managers must ensure that GCG policies and practices are implemented consistently and properly supervised to minimize risk and increase investor confidence. In addition, although ethical leadership does not show a direct effect, companies still need to promote ethical behavior to create a positive organizational culture that supports long-term business sustainability